The family context of parenting in children's adaptation to elementary school - Cowan, Philip A. (Monographs in parenting series., 2005)
This work is a result of a longitudinal prevention study of 100 families begun the year before their first children entered kindergarten. The text focuses on how parent-child relationships are not the only determinants of a child's academic competence, social competence, and behavior.